ECONOMIC PROBLEMS OF EDUCATION DEVELOPMENT UNDER THE WORLD FINANCIAL CRISIS - A. L. Kurakov (Russian Journal of Economics and Law)
The economic condition of the Russian education system is studied. The main problems of education financial provision under the world financial crisis are revealed. The main sources of professional education financing are defined. Approaches to modernization and efficiency development of the education state financing are suggested. The man directions of modernization of non-budget financing in education sphere are presented.